Database of embedment parameters from soft- and hardwoods - Schweigler, Michael (Linnaeus University, 2019)
The database includes embedment parameters from in total 1565 tests, taken from 7 reports originating from ENSTIB/LERMaB Epinal, Vienna University of Technology (IMWS, TU Wien), Linnaeus University Växjö (LNU), TU Delft and Karlsruhe Institute of Technology (KIT).It compromises parameters from embedment test on 6 soft- and hardwood spieces, 4 wood-based products, 4 dowel diameter, loaded at 7 different load-to-grain angles.

The embedment parameters can be used to describe load-displacement curves of steel dowels embedded in wood, being exploited in numerical models for single-dowel connections.

Embedment parameters given in the database are explained and discussed in:Schweigler, M., T. K. Bader, J.F. Bocquet, and C. Sandhaas (2019). "Embedment test analysis and data in the context of phenomenological modeling for dowelled timber joint design." In: Proceedings of INTER/52-07-08 , Tacoma, USA.

Update:2020-07-06: Parameters from embedment tests on birch (solid timber) are added Benistand, T. (2020).


The database includes embedment parameters taken from following reports:

Benistand, T. (2019). “Comportements structurels des Essences de bois feuillus français en vue de leur meilleure intégration aux Eurocodes 5.” PhD thesis. University of Lorraine, France (in progress).

Benistand T, Bleron L., Bocquet J.F (2020) " Embedding Strength Prediction for European Hardwood Species" In: Proceedings INTER/53-07-9.

Blaß, H. J. and T. Uibel (2007). “Tragfähigkeit von stiftförmigen Verbindungsmitteln in Brettsperrholz (in German)”. In: Karlsruher Berichte zum Ingenieurholzbau Band 8.

Lemaître, R. (2020). “Développement d’un outil de calcul non linéaire de dimensionnement d’assemblages bois tridimensionnels soumis à des torseurs plans.” PhD thesis. University of Lorraine, France.

Sandhaas, C., G.J.P. Ravenshorst, H.J. Blass, and J.W.G. van de Kuilen (2013). “Embedment tests parallel-to-grain and ductility aspects using various wood species”. In: European Journal of Wood and Wood Products 71(5), pp. 599–608.

Schweigler, M., T. K. Bader, G. Hochreiner, G. Unger, and J. Eberhardsteiner (2016). “Load-to-grain angle dependence of the embedment behavior of dowel-type fasteners in laminated veneer lumber”. In: Construction and Building Materials 126, pp. 1020–1033.

Schweigler, M., T. K. Bader, J. Vessby, and J. Eberhardsteiner (2017). “Constrained displacement boundary conditions in embedment testing of dowel-type fasteners in LVL”. In: Strain 53(6). DOI: 10.1111/str.12238.



The dataset was originally published in DiVA and moved to SND in 2024.
Database of embedment parameters from soft- and hardwoods
Keywords: wood; trä; trees; träd; hardwood trees; ädla träd; tree species; trädslag; Civil engineering; Byggteknik; Building Technologies; Husbyggnad